Immanence, Transcendence and Thinking Life with Deleuze and Eckhart. Issue 1 (1st June 2013) - Haynes, Patrice
Abstract: This paper questions the post-Nietzschean, materialist assumption that divine transcendence is necessarily inimical to life. In light of Eugene Thacker's distinction between Life and the living, this paper explores the concept of life in the works of Meister Eckhart and Gilles Deleuze, two thinkers who, when read alongside each other, reveal how the notions of absolute transcendence and absolute immanence invert into each other. One consequence of such inversion is that both thinkers face the question of how to think life in relation to nothingness. While it might seem that Eckhart's negative theology confirms the Nietzschean suspicion that divine transcendence is anti-life, the paper seeks to forestall such a conclusion by showing how Eckhart's apophaticism is better able to uphold the integrity of this-worldly life than Deleuze's immanentism. However, the paper ultimately criticises both thinkers for failing to affirm the value of finite, creaturely life in itself .